Proceedings of the Proceedings of the 1st Workshop on Multidisciplinary and Its Applications Part 1, WMA-01 2018, 19-20 January 2019
DOI: 10.4108/eai.20-1-2018.2281951
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Good Corporate Governance, Return On Asset, and Firm Size on Firm Value in LQ45 Company Listed in Indonesia Stock Exchange

Abstract: This research objective was to know the influence of Good Corporate Governance, Return On asset, and Firm Size to Firm Value On Company Registered in LQ45. Population The Grand Theory in this research are Agency Theory and Signaling Theory. Sampling method used is Purposive Sampling. The population of this research ware 45 companies of LQ45 and the sampples ware 12 companies of LQ45 indonesia during the period of 2012-2015. Data Analysis Technique used was Multiple Regression Linear. This results partially sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
0
0
3
Order By: Relevance
“…When ROA was employed as a measure of financial performance, the findings of this study observed a positive and significant association between firm size and corporate governance index. The findings are congruent with those of Widiyanti et al (2018) and Benvenuto et al (2021), who established a positive and significant association between the firm size and the corporate governance index of the financial institutions. Therefore, larger firm sizes improve corporate governance index practices.…”
Section: Results and Discussion Of Findingssupporting
confidence: 86%
“…When ROA was employed as a measure of financial performance, the findings of this study observed a positive and significant association between firm size and corporate governance index. The findings are congruent with those of Widiyanti et al (2018) and Benvenuto et al (2021), who established a positive and significant association between the firm size and the corporate governance index of the financial institutions. Therefore, larger firm sizes improve corporate governance index practices.…”
Section: Results and Discussion Of Findingssupporting
confidence: 86%
“…Hasil penelitian, Profitabilitas yang diukur melalui ROA akan memberi pengaruh signifikan dengan arah pengaruh positif terhadap nilai perusahaan yang diukur melalui Tobin's Q (Agustina, 2020;Fajaria & Isnalita, 2018;Hutabarat & Sihotang, 2020;Dang, Vu, Ngo, & Hoang, 2019;Alifia & Sanusi, 2021;Zuhroh I. , 2019;Widiyanti, Saputri, Ghasarma, & Sriyani, 2019;Septyanto & Nugraha, 2021). Tetapi berbeda dengan Suhendry et al, (2021) yang menyatakan ROA tidak berpengaruh terhadap nilai perusahaan.…”
Section: Pengembangan Hipotesisunclassified
“…Penelitian yang melakukan pengujian mengenai nilai perusahaan telah banyak dilakukan oleh beberapa peneliti sebelumnya. Nilai perusahaan yang dilakukan pengujian dengan pengungkapan manajemen risiko (Ardianto & Rivandi, 2018;Chairani & Siregar, 2021;Devi et al, 2017;Emar & Ayem, 2020;Florio & Leoni, 2017;Horvey & Ankamah, 2020;Iswajuni et al, 2018;Siregar & Safitri, 2019), tata kelola perusahaan (Farooq et al, 2021;Firmansyah, Husna, & Putri, 2021;Hapsari, 2018;Haryono & Paminto, 2015;Irawan & Devie, 2017;Laurensia, 2018;Mumtazah & Purwanto, 2020;Mutmainah, 2015;Owusu & Weir, 2016; M. M. Putri et al, 2020;Sitorus & Sitorus, 2017;Susilo et al, 2018;Widiyanti et al, 2019), modal intelektual (Devi et al, 2017Emar & Ayem, 2020;Gaol et al, 2021;Juwita & Angela, 2016), emisi karbon (Alfayerds & Setiawan, 2021;Firmansyah, Jadi, Febrian, & Fasita, 2021;Rusmana & Purnaman, 2020;Zuhrufiyah & Anggraeni, 2019), profitabilitas (Iswajuni et al, 2018;Mumtazah & Purwanto, 2020;Wijaya & Sedana, 2015), tanggung jawab sosial (Butt et al, 2020;Gaol et al, 2021;Guo et al, 2020), struktur modal (Hirdinis, 2019;Luu, 2021), koneksi politik (Bandiyono, 2019;Supatmi et al, 2...…”
Section: Gambar 1 Pertumbuhan Kegiatan Usaha Perbankan DI Indonesiaunclassified
“…Sementara itu, penelitian Firmansyah, Husna, et al (2021), Hapsari (2018, Haryono & Paminto (2015), M. M. Putri et al (2020), Susilo et al (2018) menyimpulkan bahwa tata kelola perusahaan tidak berpengaruh terhadap nilai perusahaan. Selanjutnya, Mutmainah (2015), Sitorus & Sitorus (2017), Widiyanti et al (2019) menemukan bahwa tata kelola perusahaan berpengaruh negatif terhadap nilai perusahaan. Dengan demikian, pengujian tata kelola perusahaan terhadap nilai perusahaan perlu dilakukan kembali.…”
Section: Gambar 1 Pertumbuhan Kegiatan Usaha Perbankan DI Indonesiaunclassified